Multiplatform-Based Educational Game of Islamic History in Walisongo Era - Nisa, Khoirun; Sudarmilah, Endah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Islam arrived in Indonesia through various intermediaries. One of its dissemination ways was through preaching brought by Walisongo (nine saints). When learning history, most children are bored because the textbook only contains written texts, which are less interesting for them. The purpose of this research was to develop a multiplatform-based educative game as an interactive learning media. The methodology of this research was SDLC method (System Development Life Cycle) which was derived into a stage of system systematically starting from planning, analysis, design, implementation, testing and caring. The testing of this research used the testing of black box and usability by using questionnaire for the respondents who had used the educative game. The result of this research was a learning medium in the form of an educative game built by using the multiplatform-based construct.